Hausdorff diameter of a nonsymmetric class of vector functions - Polovina, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
In the space of parametrically determined m-dimensional curves with the Hausdorff metric, we find the diameter of a class of curves whose coordinate functions satisfy the Lipschitz condition on some segment and take fixed values at its endpoints. We obtain the dependence of relations determining the value of the diameter on the evenness of m.